DESKRIPSI PANGGILAN ORANG MUDA DALAM HIDUP MENGGEREJA DI STASI EMMANUEL BATU AMPAR - Maru, Maria Ines Teresa; Wulung, F.X. Heryatno Wono (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
The calling of young individuals in church life encompasses a broad understanding. Many young people still lack a proper comprehension of the essence of the calling to church life. Hence, this article aims to provide an understanding of the essence and nature of the calling of young individuals in church life through several Church documents. The article is composed using a qualitative research method with a phenomenological research design and employs data collection techniques such as documentation studies, observations, and interviews. The research findings reveal that young Catholic individuals at Stasi Emmanuel Batu Ampar interpret the term